A new 2D auxetic CN2 nanostructure with high energy density and mechanical strength. Issue 7 (15th February 2021) - Wei, Qun; Yang, Ying; Gavrilov, Alexander; Peng, Xihong
Abstract : The existence of a new two dimensional CN2 structure was predicted using ab initio molecular dynamics (AIMD) and density-functional theory calculations. Abstract : The existence of a new two dimensional CN2 structure was predicted using ab initio molecular dynamics (AIMD) and density-functional theory calculations. It consists of tetragonal and hexagonal rings with C–N and N–N bonds arranged in a buckling plane, isostructural to the tetrahex-carbon allotrope. It is thermodynamically and kinetically stable suggested by its phonon spectrum and AIMD. This nanosheet has a high concentration of N and contains N–N single bonds with an energy density of 6.3 kJ g −1, indicating its potential applications as a high energy density material. It possesses exotic mechanical properties with a negative Poisson's ratio and an anisotropic Young's modulus. The modulus in the zigzag direction is predicted to be 340 N m −1, stiffer than those of h-BN and penta-CN2 sheets and comparable to that of graphene. Its ideal strength of 28.8 N m −1 outperforms that of penta-graphene. The material maintains phonon stability upon the application of uniaxial strain up to 10% (13%) in the zigzag (armchair) direction or biaxial strain up to 5%. It possesses a wide indirect HSE band gap of 4.57 eV, which is tunable between 3.37–4.57 eV through strain. Double-layered structures are also explored. Such unique properties may facilitate its potential applications as a high energy density material and in nanomechanics and electronics.